Tumor invasion to the spinal region after primary surgery: A case report - Zahra Davudi; Arezoo Chouhdari; Guive Sharifi; Nader Akbari dilmaghani (Babol University of Medical Sciences, 2021)
Background: It is believed that pituitary carcinoma is a rare disorder and arise from the transformation of benign invasive macroadenomas, and the process of this transformation takes place slowly. Case Presentation: A 51-year-old man presented with the clinical features of Cushing syndrome and walking impairment who was diagnosed with metastatic corticotroph pituitary carcinoma to the spine region, 6 years after the initial resection of a primary invasive pituitary adenoma. He made a visit to neurosurgery and endocrinology clinic with the chief complaint of weight gain, facial and extremities swelling, paresthesia, weakness, motion and speaking impairments, and HTN which all appeared through the last 1 year; hormonal laboratory tests showed urine free cortisol (UFC) 197.8 and 367. 30 ug/24hrs (36-137), cortisol 8 am after 1 mg overnight dexamethasone test 375 ng/mL (50-250) and ACTH 59 pg/mL. MRI study revealed a mass in the brainstem with the compression effect on spinal region, pituitary imagine does not differ from the last MRI. He underwent a neurosurgery for spinal mass resection, which was successful and the total mass was resected. After surgery, the patientchr('39')s condition became better. Conclusion: Pituitary carcinoma is a rare entity impossible to recognize as a primary tumor because its diagnosis by definition requires the presence of metastasis. Clinical awareness of the rare possibility for aggressive adenomas will progress, to metastasize is essential to appropriately monitor patients for possible early detection and treatment of pituitary carcinoma.